Penium amplificatum status nova (Desmidiales, Streptophyta) - van Westen, Marien; Coesel, Peter (Phytotaxa, 2012)
From extensive field studies in the Dutch province of Drenthe and comparative literature research it appeared that Penium spirostriolatum var. amplificatum differs from the nominate variety of Penium spirostriolatum not only by its capitate cell ends but also by coarser and more spiralized ridges on the cell wall and by distinctly different ecological demands. Var. amplificatum, found in 23 Drenthian locations, occurred exclusively in samples with pH<5 whereas var. spirostriolatum, encountered in 25 other locations, was found predominantly in water with pH>5 (up to 7.3). Based on their results the authors propose to raise var. amplificatum to species rank: Penium amplificatum stat. nov.